Enhanced Series Cascade Control Strategies for Unstable Processes - Raja, G. Lloyds; Ali, Ahmad (2018 4th International Conference on Electrical Energy Systems (ICEES), 2018)
Series cascade control structures with and without delay compensator are proposed for unstable processes with large and small dead time, respectively. The proposed series cascade control structure (SCCS) for process models with small dead time has three controllers: primary controller, secondary controller and stabilizing controller. Secondary controller is designed using internal model control approach whereas the primary controller is designed as a proportional-integral (PI) controller using the method of moments. The stabilizing controller is designed as a proportional-derivative (PD) in series with lead-lag filter using direct synthesis approach. For unstable process models with large time delay, a Smith predictor is included in the outer loop in addition to the above controllers. Furthermore, a first order lag filter is also included to enhance the robustness of the proposed Smith predictor based SCCS. Necessary guidelines are provided for the user to select suitable values of closed-loop time constants. Simulation studies indicate that the proposed strategies yield enhanced and robust closed-loop performance than the contemporary works.